Environmental Management Accounting Disclosure and Market Valuation: A Critical Analysis of ESG Performance Impact on Stock Price Volatility in Indonesia Stock Exchange Listed Companies - Arthur Simanjuntak; Thomas Sumarsan Goh; Farida Sagala; David Patar Sitangggang; Heri Imanuel Nadeak (Owner : Riset dan Jurnal Akuntansi, 2026)
Purpose: This research investigates the relationship between Environmental Management Accounting (EMA) disclosure quality and market valuation, specifically examining how ESG performance mediates the impact on stock price volatility among Indonesia Stock Exchange (IDX) listed companies. The study explores how comprehensive environmental accounting disclosures influence investor behavior and market dynamics within emerging capital markets. Method: This study employs a quantitative approach using panel data regression analysis with fixed effects modeling. The research sample comprises 180 IDX-listed companies across various sectors from 2019-2023, generating 900 firm-year observations. Data analysis was conducted using STATA 18.0 to examine the relationships between EMA disclosure quality, ESG performance, and stock price volatility while controlling for firm-specific characteristics and market conditions. Findings: The results demonstrate that EMA disclosure quality significantly reduces stock price volatility (? = -0.428, p < 0.001) and enhances ESG performance scores (? = 0.634, p < 0.001). ESG performance serves as a partial mediator, explaining 42.7% of the total effect of EMA disclosure on stock price volatility. The model explains 58.4% of stock price volatility variance, indicating strong explanatory power of environmental accounting disclosures in market valuation dynamics. Novelty: This study provides the first comprehensive empirical evidence linking environmental management accounting disclosure practices with capital market outcomes in an emerging market context. The research contributes to the literature by demonstrating how environmental accounting transparency creates value through reduced information asymmetry and enhanced ESG performance, ultimately stabilizing stock price movements.